Long-Term Health Associated with Small and Large for Gestational Age Births among Young Thai Adults - Alisha Suhag; Amaraporn Rerkasem; Kanokwan Kulprachakarn; Wason Parklak; Chaisiri Angkurawaranon; Kittipan Rerkasem; José G. B. Derraik (Children, 2022)
We examined the long-term health outcomes associated with being born small for gestational age (SGA) or large for gestational age (LGA). A total of 632 young adults aged ≈20.6 years were recruited from a longitudinal study (Chiang Mai, Thailand) in 2010: 473 born appropriate for gestational age (AGA), 142 SGA, and 17 LGA. The clinical assessments included anthropometry, blood pressure (BP), lipid profile, and an oral glucose tolerance test (OGTT). Young adults born SGA were 1.8 and 3.2 cm shorter than AGA (p = 0.0006) and LGA (p = 0.019) participants, respectively. The incidence of short stature was 8% among SGA compared with 3% in AGA and no cases among LGA participants, with the adjusted relative risk (aRR) of short stature among SGA 2.70 times higher than that of AGA counterparts (p = 0.013). SGA participants also had a 2 h glucose 7% higher than that of the AGA group (105 vs. 99 mg/dL; p = 0.006). Young adults born LGA had a BMI greater by 2.42 kg/m2 (p = 0.025) and 2.11 kg/m2 (p = 0.040) than those of SGA and AGA, respectively. Thus, the rate of overweight/obesity was 35% in the LGA group compared with 14.2% and 16.6% of SGA and AGA groups, respectively, with corresponding aRR of overweight/obesity of 2.95 (p = 0.011) and 2.50 (p = 0.017), respectively. LGA participants had markedly higher rates of BP abnormalities (prehypertension and/or hypertension) with an aRR of systolic BP abnormalities of 2.30 (p = 0.023) and 2.79 (p = 0.003) compared with SGA and AGA groups, respectively. Thai young adults born SGA had an increased risk of short stature and displayed some impairment in glucose metabolism. In contrast, those born LGA were at an increased risk of overweight/obesity and elevated blood pressure. The long-term follow-up of this cohort is important to ascertain whether these early abnormalities accentuate over time, leading to overt cardiometabolic conditions.